Acute changes in sagittal plane kinematics while wearing a novel belt device during treadmill running - Greenberg, E. T.; Garcia, M. C.; Galante, J.; Werner, W. G. (Sports Biomechanics, 2022)
Somatosensory feedback is used in walking retraining; however, its utility in running is less feasible due to the greater associated speeds. The purpose of this study was to examine the acute effects of wearing a novel running belt device on sagittal plane running kinematics. Ten healthy runners ran on a treadmill with and without the use of a running belt device within a repeated measures study design. Temporal-spatial characteristics and sagittal plane knee and ankle kinematics were recorded with three-dimensional motion analysis. Wilcoxon Signed-Rank Tests revealed significant decreases in centre of mass vertical displacement (z = -2.083, p = 0.003), tibial inclination at initial contact (z = -2.803, p = 0.003), and stance phase knee joint excursion (z = -2.701, p = 0.003), and greater knee flexion at initial contact (z = -2.803, p = 0.003) when the belt was donned. No differences were observed in step rate (z = -0.351, p = 0.363), foot inclination angle at initial contact (z = -2.090, p = 0.018), or peak knee flexion during stance (z = -1.172, p = 0.121). Findings suggest that donning a running belt can minimise specific high-risk biomechanical characteristics in runners with particular kinematic profiles.